(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: This article is about the effect of music on human health and psyche. A person's character, behavior, mood, behavior, and the environment he is in are influenced by music. After all, art invites a person's heart to beauty, awakens delicate feelings and enriches his spiritual world. During the development of our people and nation, dutor, flute, gijjak, oud, rubob and other musical instruments, which are considered our national instruments along with songs, served as invaluable spiritual food.